2014
DOI: 10.1097/aln.0000000000000338
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Unnecessary Preoperative Blood Orders and Costs by Implementing an Updated Institution-specific Maximum Surgical Blood Order Schedule and a Remote Electronic Blood Release System

Abstract: Background Using blood utilization data acquired from our anesthesia information management system, an updated institution-specific maximum surgical blood order schedule (MSBOS) was introduced. We evaluate whether the MSBOS, along with a remote electronic blood release system (EBRS), reduced unnecessary preoperative blood orders and costs. Methods At a large academic medical center, data for preoperative blood orders were analyzed for 63,916 surgical patients over a 34-month period. The new MSBOS and the EBR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
57
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 28 publications
(41 reference statements)
2
57
0
Order By: Relevance
“…However, this benefit was not found in the hospital where both BBI and ERBI RBC units were collected from remote refrigerators. This confirms and builds on the findings from previous studies in single hospitals . A reduction in the time taken for blood to reach the patient was not realized when ERBI was carried out at a blood refrigerator in the blood bank.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, this benefit was not found in the hospital where both BBI and ERBI RBC units were collected from remote refrigerators. This confirms and builds on the findings from previous studies in single hospitals . A reduction in the time taken for blood to reach the patient was not realized when ERBI was carried out at a blood refrigerator in the blood bank.…”
Section: Discussionsupporting
confidence: 90%
“…There are reports from single centers of the benefits of ERBI . The objective of this study was to identify the value of ERBI in five hospitals, three of which were in England, one in Wales, and one in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports demonstrated the efficacy of ERBI systems in reducing excessive preoperative blood orders; in general, those systems required manual pick‐up of the units intended for a specific patient and a subsequent computer‐controlled check of the correct selection of these units. To the best of our knowledge, only one study in a large population has reported the efficiency of an ERBI with an automated refrigerator. That study demonstrated a decrease in the crossmatch‐to‐transfusion ratio, but the system was implemented simultaneously with a revision of the local maximum surgical blood order schedule, and the specific contribution of the ERBI to the results is unknown.…”
Section: Discussionmentioning
confidence: 99%
“…In the past, several solutions have been proven effective for more efficiently issuing blood units to surgical wards and operating rooms far from the blood bank. All of those solutions are based on the implementation of an electronic remote blood issue (ERBI) system with varying degrees of computer control . Briefly, a stock of unallocated RBC units is stored in a refrigerator close to the operating room.…”
mentioning
confidence: 99%
“…Our findings further highlight the importance of appropriate guideline-based PBT in bladder cancer patients undergoing cystectomy and should be a stimulus for institutions to have additional dialogue about the adverse effects of overuse of PBT. 3233 Moreover, a restrictive strategy for hemoglobin transfusion triggers should be strongly considered in RC patients to reduce unnecessary transfusions. While previous RCTs did not find a significant different in the primary clinical outcomes, they did not specifically study cancer patients who have received systemic chemotherapy or those given blood near the end of the 42-day shelf life.…”
Section: Discussionmentioning
confidence: 99%